80‐3: Immanent Dichromaticity in Trichromatic Observer: 2nd Coordinate in MDS Analyses of R‐G Neutral‐ and Y‐B Only Changed‐Stimuli Reflects Chromatic Saliency. Issue 1 (25th September 2020) - Hira, Shoko; Endo, Rei; Mochihara, Kanta; Ohkoba, Minoru; Ishikawa, Tomoharu; Ayama, Miyoshi; Ohtsuka, Sakuichi
Abstract : We investigate immanent dichromaticity in trichromatic observers by using MDS (Multidimensional‐Scaling). The results show that color‐constellations yielded when observing R‐G neutral‐ and Y‐B only changed‐stimuli provides strong evidence of concave‐shaped dichromic. The results of additional paired comparison tests on subjective saliency reveal that the second coordinate of MDS reflects perceived chromatic saliency.